1990
DOI: 10.1111/j.1365-2621.1990.tb05205.x
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Ice Spoilage of Albacore (Thunnus alalunga)

Abstract: The protein, lipid, water and ash contents of the liver and different parts of the muscle tissue of albacore, Thunrzus alalunga, were measured. Fish were caught at three different seasons and were separated into three size groups for analysis. There were significant diffcrenccs among the composition of the tissues; size and season also had significant effects. Fish were stored in ice, and scales for the sensory assessment of freshness were developed for raw fish and for cooked meat. Changes in total volatile b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
32
1
2

Year Published

1994
1994
2015
2015

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 22 publications
6
32
1
2
Order By: Relevance
“…In agreement with these results, other reports concerning hake (Baixas-Nogueras et al, 2002;Ru ız-Capillas & Moral, 2001) and other fish species (Fern andez-Salguero & Mackie, 1987;P erez-Villarreal & Pozo, 1990) have described sharp increases in TMA-N contents after 9-12 days of storage in conventional flake ice. In contrast with these results, the final TMA-N content determined here in the slurry ice batch was below 5 mg TMA-N/100 g muscle.…”
Section: Chemical Analysessupporting
confidence: 90%
“…In agreement with these results, other reports concerning hake (Baixas-Nogueras et al, 2002;Ru ız-Capillas & Moral, 2001) and other fish species (Fern andez-Salguero & Mackie, 1987;P erez-Villarreal & Pozo, 1990) have described sharp increases in TMA-N contents after 9-12 days of storage in conventional flake ice. In contrast with these results, the final TMA-N content determined here in the slurry ice batch was below 5 mg TMA-N/100 g muscle.…”
Section: Chemical Analysessupporting
confidence: 90%
“…In the case of a higher size fish, TMA levels showed a sharp increase only after 20 days during albacore tuna storage (Pérez-Villarreal and Pozo, 1990), according to the sensory assessment mentioned.…”
Section: Amine Formation and Nucleotide Degradationmentioning
confidence: 89%
“…Nucleotide degradation (ATP) has been observed to occur leading to a progressive formation of hypoxanthine with storage time in sardine (Nunes et al, 1992), horse mackerel (Smith et al, 1980) and salmon (Erikson et al, 1997); employment of the k-value showed a great correlation with sensory assessment and the storage time in albacore (Pérez-Villarreal and Pozo, 1990) and salmon (Erikson et al, 1997).…”
Section: Amine Formation and Nucleotide Degradationmentioning
confidence: 99%
“…Meanwhile, TMA are resulted from the reduction of trimethylamine-oxide (TMAO) by bacterial activity and intrinsic enzymes. It is often used as an index of freshness of fish and fish products (Hush 1988;Villareal and Pozo, 1990). The levels of TVB and TMA that have been considered as the upper limit in fishery products are 30 -35 mg/ 100 g (Hush, 1988;Sikorski et al, 1989;Connell, 1995) and 10 -15 mg/ 100 g (Sikorski et al, 1989;Connell, 1995).…”
Section: Introductionmentioning
confidence: 99%